The Pros and Cons of Implementing Local Regulation Number 17 of 2019 on the Prohibition of Night Parties in North Musi Rawas District (Case Study: Karang Anyar Village, Rupit Sub-District) - Andini, Alifiya (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2023)
This article examines the advantages and disadvantages of enacting Regional Regulation Number 17 of 2019 concerning the Prohibition of Evening Parties in North Musi Rawas Regency, with a case study conducted in Karang Anyar Village, Rupit District. The study aims to explore both the positive and negative aspects of implementing this regulation and how the monitoring system for evening party entertainment in North Musi Rawas Regency aligns with Regulation Number 17 of 2019. The central issue addressed in this study pertains to understanding the reasons behind the pros and cons surrounding the regulation's prohibition of night parties in North Musi Rawas Regency and the corresponding monitoring mechanisms. The research methodology employed in this study is qualitative, utilizing descriptive analysis. The Actor Theory proposed by Anthony Giddens and theories of interest groups and pressure groups serve as the theoretical framework. Primary data, obtained through direct interviews, and secondary data from online news sources, local government archives, and Karang Anyar Village archives, are utilized. Data collection methods include interviews and documentation. The indings reveal that proponents of the regulation support it due to concerns regarding night parties being associated with drug trafficking, alcohol consumption, and other negative activities. Conversely, opponents of the regulation advocate for a curfew until 24:00 WIB instead of a complete ban, citing the cultural practice of the Night Party Association in Karang Anyar Village. These associations involve social gatherings in the evening, where participants contribute financially or otherwise in accordance with established customs and regulations.